Implementation of PSAK 112 Improves Productive Waqf Management: Penerapan PSAK 112 Meningkatkan Pengelolaan Wakaf Produktif - Mhd. Farhan Mukti; Yenni Samri Juliati Nasution; Tuti Anggraini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Waqf, a cornerstone of Islamic social finance, holds immense economic potential yet remains underutilized in many urban settings. Specific Background: In Medan City, the low realization of waqf collection and asset utilization highlights a lack of transparency and accountability in waqf management. Knowledge Gap: While PSAK 112 was introduced to improve waqf financial reporting, few quantitative studies have examined its practical impact, particularly in large metropolitan areas. Aim: This study investigates the effect of PSAK 112 implementation on the development of productive waqf in Medan. Results: Using a quantitative approach and linear regression on data from 30 nazhir institutions, the results show a significant positive relationship (t = 9.792, p < 0.000; R² = 0.904) between PSAK 112 implementation and productive waqf growth. Novelty: Unlike previous research focused on theoretical frameworks or regional case studies, this study provides empirical evidence from a major city with complex waqf dynamics. Implications: These findings underscore the critical role of standardized financial reporting in enhancing nazhir accountability, increasing public trust, and optimizing waqf assets. The study offers strategic recommendations for regulators and waqf authorities to support broader adoption of PSAK 112 for national waqf development.Highlight : PSAK 112 significantly boosts the development of productive waqf in Medan, explaining 90.4% of its growth variation. Transparent financial reporting enhances stakeholder trust and strengthens nazhir accountability. Implementation of PSAK 112 supports Islamic accounting theory and improves waqf governance effectiveness. Keywords : PSAK 112, Productive Waqf, Waqf Accounting, Nazir Accountability, Financial Transparency